2021
DOI: 10.1093/tbm/ibab006
|View full text |Cite
|
Sign up to set email alerts
|

What happens when the party moves home? The effect of the COVID-19 pandemic on U.S. college student alcohol consumption as a function of legal drinking status using longitudinal data

Abstract: Many young adults in the United States (U.S.) moved from college accommodations to live with their parents/family during the Spring 2020 semester due to the COVID-19 pandemic. While alcohol consumption fluctuates during a typical semester among students, the impact of the sudden changes stemming from the pandemic on students’ alcohol consumption patterns is unclear. To examine the impact of the COVID-19 pandemic on college student alcohol consumption while accounting for legal drinking age and living situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 20 publications
11
39
0
Order By: Relevance
“…Expansion of off-trade sales often occurred simultaneously to the closure of workplaces, schools, childcare, leisure and physical activity centres [ 126 ]. Although evidence is still emerging, reports in the media and grey literature suggest increased drinking in the home in some countries [ 127 , 128 , 129 ] (largely off-setting reductions in on-premises drinking). These reports have appeared alongside several studies showing increased abusive head trauma among children [ 130 ] and family violence [ 131 , 132 ].…”
Section: Effective Interventions and Policiesmentioning
confidence: 99%
“…Expansion of off-trade sales often occurred simultaneously to the closure of workplaces, schools, childcare, leisure and physical activity centres [ 126 ]. Although evidence is still emerging, reports in the media and grey literature suggest increased drinking in the home in some countries [ 127 , 128 , 129 ] (largely off-setting reductions in on-premises drinking). These reports have appeared alongside several studies showing increased abusive head trauma among children [ 130 ] and family violence [ 131 , 132 ].…”
Section: Effective Interventions and Policiesmentioning
confidence: 99%
“…Studies of alcohol use in United States (U.S.) college students have produced conflicting results with reference to changes related to COVID. On the one hand, two studies suggested increases in alcohol use ( Charles et al, 2021 ; Lechner et al, 2020 ), while three studies found decreases in alcohol use following university closures ( Jaffe et al, 2021 ; Ryerson et al, 2021 ; White et al, 2020 ). A sixth found a complex pattern of changes, with increases in frequency of use that were counteracted by declines in quantity of use and binge drinking, all of which was moderated by pre-COVID use patterns ( Jackson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature has investigated the effects of the pandemic on alcohol use among adolescents, young adults, and college students in the U.S. and found mixed results [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Decreases in opportunities to socialize related to the pandemic were associated with decreases in alcohol use among college students [ 11 , 12 , 18 , 20 ].…”
mentioning
confidence: 99%
“…A growing literature has investigated the effects of the pandemic on alcohol use among adolescents, young adults, and college students in the U.S. and found mixed results [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Decreases in opportunities to socialize related to the pandemic were associated with decreases in alcohol use among college students [ 11 , 12 , 18 , 20 ]. College students who changed residence to live with parents and those who believed that Covid-19 precaution-taking was important, which presumably was associated with fewer opportunities to socialize, decreased their alcohol use more than their peers [ 11 , 12 , [18] , [19] , [20] ].…”
mentioning
confidence: 99%
See 1 more Smart Citation